2009
DOI: 10.1007/s00198-009-1065-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy distal radius fractures in middle-aged and elderly women—seasonal variations, prevalence of osteoporosis, and associates with fractures

Abstract: Our study highlights that environmental factor, as well as osteoporosis are associated with distal radius fractures in middle-aged and elderly women. Osteoporosis is also frequently found in outdoor patients, thus, all female distal radius fracture patients >or=50 years should be referred for osteoporosis assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 34 publications
6
33
0
Order By: Relevance
“…[5][6][7] Increased risk secondary to fracture lasts up to 10 years. Therefore, 40-60% of the surviving men and women were observed to experience another fracture later on.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Increased risk secondary to fracture lasts up to 10 years. Therefore, 40-60% of the surviving men and women were observed to experience another fracture later on.…”
Section: Discussionmentioning
confidence: 99%
“…55,58 When health conditions exist, which cause both loss of bone strength (eg, OP) and deficits in dynamic balance (eg, chronic stroke or diabetic neuropathy), the incidence of falls and the associated risk of DRF increase. [59][60][61][62] Prognostic factors…”
Section: Risk Factorsmentioning
confidence: 99%
“…A study from Norway suggested that there is seasonal variation only in those distal radius fractures sustained outdoors [31]. We could not assess whether the falling incidents had occurred indoors or outdoors, as we did not have the resources to interview the patients.…”
Section: Ao Classificationmentioning
confidence: 99%